Use of the small-bites fascial closure technique and strategies to improve adoption: mixed-methods study. Issue 10 (9th July 2021) - Dossa, F; Speller, B; Acuna, S A; Adessky, R; Facey, M; Baxter, N N
Abstract : In a mixed-methods study of general surgeons and general surgery residents, only 26 per cent of surgeons reported routine use of the small-bites fascial closure technique. Major barriers to adoption included surgical dogma, distrust in the technique, and the generalizability/applicability of existing evidence.